Spectrally and angularly resolved measurements of three-halves harmonic emission from laser-produced plasmas. (24th August 2017) - Kang, N; Liu, H; Lin, Z; Lei, A; Zhou, S; Fang, Z; An, H; Li, K; Fan, W
Abstract: Spectra of three-halves harmonic emissions (3 ω 0 /2) from laser-produced plasmas were measured at different angles, including both forward and backward sides, from the direction of incident laser beams. The 3 ω 0 /2 emitted from carbon–hydrogen (CH) targets was observed to be larger than that from aluminum (Al) targets with the same incident laser intensity, which supports the argument that the two-plasmon decay (TPD) instability could be inhibited by using medium-Z ablator instead of CH ablator in direct-drive inertial confinement fusion. Besides, the measured 3 ω 0 /2–incident intensity curves for both materials suggest relatively lower threshold of TPD than the calculated values. In experiments with thin Al targets, the angular distribution of the blue- and red-shifted peaks of 3 ω 0 /2 spectra were obtained, which shows that the most intense blue- and red-shifted peaks may not be produced in paired plasmons, but the spectra produced by their 'twin' plasmons were not observed. Because 3 ω 0 / 2 may have been influenced by other physical processes during their propagation from their birth places to the detectors, the mismatches on emission angle, wavelength shift, and threshold may be qualitatively explained through the assumption that small-scale light filaments widely existed in the corona of laser-produced plasmas.